1997
DOI: 10.1080/00365519709056385
|View full text |Cite
|
Sign up to set email alerts
|

Serum and renal IGF-I levels after uninephrectomy in the rat

Abstract: The hypertrophy of the remaining kidney following uninephrectomy (UNx) has been related to an increase in renal insulin growth factor-I (IGF-I) content. However, while the increase in renal IGF-I lasts for only days after UNx, renal hypertrophy continues for months. In the present study we investigated whether IGF-I also plays a role in the late post uninephrectomy growth of the remaining kidney. Renal IGF-I in the remnant kidney was greater than that of control kidneys (78.3 +/- 17.3 vs 56.0 +/- 14.0 pmol g-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Proliferation of tubular epithelial cells is crucial for renal recovery following IRI [ 15 ]. UNx stimulates a wide range of growth factors such as IGF-1 [ 16 , 17 ], GH [ 18 , 19 ], HGF [ 20 ], VEGF [ 21 ] and EGF [ 22 , 23 ] with beneficial pleiotropic effects (e.g. proliferative, anti-apoptotic and tubulogenic as well as vasodilatory properties) [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation of tubular epithelial cells is crucial for renal recovery following IRI [ 15 ]. UNx stimulates a wide range of growth factors such as IGF-1 [ 16 , 17 ], GH [ 18 , 19 ], HGF [ 20 ], VEGF [ 21 ] and EGF [ 22 , 23 ] with beneficial pleiotropic effects (e.g. proliferative, anti-apoptotic and tubulogenic as well as vasodilatory properties) [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…3). A number of experiments have shown that compensatory hypertrophy and hyperfunction of nephrons occurs in the remaining kidney of animals who have undergone UNX due to the induction of a number of growth factors such as insulin-like growth factor [20] and hepatocyte growth factor [21,22,23]. A similar mechanism may be responsible for the enhanced development of transplanted metanephroi in UNX and pregnant recipients.…”
Section: Resultsmentioning
confidence: 97%
“…This may result from upregulated factor(s) in the circulation of the pregnant recipient facilitating angiogenesis and/or organogenesis. A number of growth factors, including IGF-I, IGF-II and HGF, are highly upregulated during pregnancy [24, 25], and HGF and IGFs participate in post-UNX renal hypertrophy [20, 23]. Pregnancy has long been cited as an aggravating factor for tumorigenesis, a process dependent upon enhanced angiogenesis [26], suggesting circulating angiogenic factors may indeed contribute to the improved success of transplants in pregnant recipients.…”
Section: Resultsmentioning
confidence: 99%